Palladium‐Catalyzed Arylation of Olefins by Triarylphosphines via CP Bond Cleavage. Issue 1 (January 2015) - Lu, Dapeng; Xu, Yu; Liu, Wenjing; Guo, Lijuan; Sun, Xingxia
Abstract CH Arylation of olefins by triarylphosphines via CP bond cleavage has been achieved with either Pd0 or PdII catalysts. A variety of olefins and triarylphosphines are tolerated, and we inferred that both Pd0 and PdII could function directly without pre‐oxidation or pre‐reduction.